Implications and Consequences of the Arms Trade Treaty (ATT) - Crovetto, Laura; Caponigro, Dario (Politikon: The IAPSS Journal of Political Science, 2016)
The international sales volume of conventional arms has been considerably increasing, making it necessary to create an international normative framework of regulations: the adoption of the ATT by the United Nations (U.N.) General Assembly (2013) represents a historical achievement to establish global standards for the arms trade, with the purpose of supporting international peace and security and curbing human-rights abuses. This paper describes the process aimed at regulating the legal arms trade and strengthening the fight against the illicit trafficking. Through the data of the U.N. Disarmament Affairs, the Stockholm International Peace Research Institute and the International Institute for Strategic Studies, the amount of conventional arms transfers worldwide has been analyzed. The articles of the ATT are illustrated focusing on the most innovative and critical dispositions. In conclusion, the Conference of the State Parties will face the turbulent developments and the different international perspectives for the future of the ATT.